De beste stuurgroep staat aan wal. Een antwoord op kritische opmerkingen van Karel Davids en anderen over het prioriteitsprogramma 'De Nederlandse cultuur in Europese context' - D. Fokkema; F. Grijzenhout (BMGN: Low Countries Historical Review, 2002)
Douwe Fokkema, Frans Grijzenhout The authors take issue with the critical remarks that were levelled at the research project 'Dutch Culture in its European Context' and, in particular, those made about the series entitled Rekenschap: 1650-2000 which they edited. They maintain that Dutch culture was correctly depicted as a 'debating culture' ; one in which consensus was actively pursued and which in turn led to compromises being reached. Open debates were feasible because of the small-scale nature of the discussions and the absence of a powerful aristocracy or any other strict hierarchical social structure, for example in ecclesiastical quarters. The project focussed on the cultural exchange with other nations rather than on giving a description of the cultural identity of the Netherlands. It was inspired by the idea of a united Europe.